Ring-opening polymerization of l-lactide and ε-caprolactone catalyzed by versatile tri-zinc complex: Synthesis of biodegradable polyester with gradient sequence structure. (January 2016) - Lin, Limiao; Xu, Yonghang; Wang, Shuanjin; Xiao, Min; Meng, Yuezhong
Graphical abstract: Highlights: A gradient poly(lactide- grad -caprolactone) was synthesized at first time. Both copolymer composition and structure have great impacts on their properties. This method can be used to synthesize biodegradable aliphatic polyester with a diverse range of properties. Abstract: An economic and biocompatible Schiff base tri-zinc catalyst was used to synthesize homo/copolymers ofl -lactide (LA) and ε-caprolactone (CL) in bulk at first time. Both 1 H and 13 C NMR analyses show that LA is more active than CL, resulting in a poly(LA- grad -CL) copolymer with gradient sequence structure. A series of copolymers containing varying LA/CL ratios were readily synthesized. The chemical structure of poly(LA- grad -CL) was fully investigated using NMR and GPC technologies. TGA, DSC, DMA and nanoindentation instruments were employed to evaluate thermal and mechanical properties of these polymers. The results indicate that polymer composition and chain structure have a great impact on the crystallization behavior and crystallinity, as well as the thermal and mechanical properties of the copolymers. Therefore, the performance of the copolymer can be then tailored by simply adjusting the ratios of LA to CL.